Intermediate and long-term residual cardiovascular risk in patients with established cardiovascular disease treated with statins - Vijayaraghavan, K.; Baum, S.; Desai, N. R.; Voyce, S. J. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Statins remain the first-line treatment for secondary prevention of cardiovascular (CV) events, with lowering of low-density lipoprotein cholesterol (LDL-C) being their therapeutic target. Although LDL-C reduction significantly lowers CV risk, residual risk persists, even in patients with well-controlled LDL-C; thus, statin add-on agents that target pathways other than LDL-C, such as the omega-3 fatty acid eicosapentaenoic acid, may help to further reduce persistent CV risk in patients with established CV disease. Methods: This narrative review examines the contemporary literature assessing intermediate- and long-term event rates in patients with established CV disease treated with statins. Results: CV event rates among patients treated with statins who have established CV disease, including coronary artery disease, cerebrovascular disease, or peripheral arterial disease, accumulate over time, with a cumulative incidence of CV events reaching up to approximately 40% over 10 years. Recurrent stroke occurs in up to 19% of patients seven years after a first cerebrovascular event. Repeat revascularization and CV-related death occurs in up to 38% and 33% of patients with peripheral artery disease after three years, respectively. Discussion: Additional treatment strategies, such as eicosapentaenoic acid, are needed to reduce persistent CV risk in patients with established CV disease treated with statins.